2021
DOI: 10.3389/fimmu.2021.680845
|View full text |Cite
|
Sign up to set email alerts
|

Immunity, Sex Hormones, and Environmental Factors as Determinants of COVID-19 Disparity in Women

Abstract: The current coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome virus 2 (SARS-CoV-2), has resulted in a major global pandemic, causing extreme morbidity and mortality. Few studies appear to suggest a significant impact of gender in morbidity and mortality, where men are reported at a higher risk than women. The infectivity, transmissibility, and varying degree of disease manifestation (mild, modest, and severe) in population studies reinforce the importance of a number of genetic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 108 publications
(121 reference statements)
1
15
0
Order By: Relevance
“…However, the male patients with severe COVID-19 expressed greater levels of CCR2 and DPP9 mRNA than female with same disease form. It has been reported that COVID-19-related mortality and morbidity are greater in male patients compared to female ( Rehman et al, 2021 , Chen et al, 2020 ). Moreover, profound differences have been indicated between male and female concerning the immunologic and inflammatory responses ( Rehman et al, 2021 ).…”
Section: - Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the male patients with severe COVID-19 expressed greater levels of CCR2 and DPP9 mRNA than female with same disease form. It has been reported that COVID-19-related mortality and morbidity are greater in male patients compared to female ( Rehman et al, 2021 , Chen et al, 2020 ). Moreover, profound differences have been indicated between male and female concerning the immunologic and inflammatory responses ( Rehman et al, 2021 ).…”
Section: - Discussionmentioning
confidence: 99%
“…It has been reported that COVID-19-related mortality and morbidity are greater in male patients compared to female ( Rehman et al, 2021 , Chen et al, 2020 ). Moreover, profound differences have been indicated between male and female concerning the immunologic and inflammatory responses ( Rehman et al, 2021 ). Whether these differences can influence chemokine responses (such as MCP-1/CCR2 pathway) and regulatory mechanisms (such as DPP9) need to be described in future investigations.…”
Section: - Discussionmentioning
confidence: 99%
“…Androgens' modulation in the immunological response to COVID-19 seems to be likewise in conflict. Studies on infected male mice have claimed a higher viral load and more inflammatory monocytes and macrophages [85]. These results could potentially correspond to the so-called 'cytokine storm' image present in most severe COVID-19 cases, where the hyperactivity of the immune system results in elevated concentrations of IL-6, IL-1, TNF-α, IFN-γ, and other proinflammatory cytokines [87].…”
Section: Sex Hormones and The Immune Systemmentioning
confidence: 97%
“…The mechanisms of regulation of ACE-2 receptors by estrogens are in fact under investigation also as adjuvant therapy for the disease [84]. Many studies on animals support the protecting role of estrogens by observing worse COVID-19 outcomes in infected female mice undergoing ovariectomy or treated with estrogen receptor inhibitors [85]. The improving or deteriorating progression of the disease but also the susceptibility to infection have been markedly ascribed to the levels of female hormones present during the lifespan even if the process is still not fully clarified.…”
Section: Sex Hormones and The Immune Systemmentioning
confidence: 99%
“…2 Furthermore, immune activation has been a long-term goal for treating immunosuppressive diseases and preventing infectious diseases. 3,4 Conventional immunostimulants potentiate antitumor immune responses and induces tumor regression; however, this often results in adverse inflammatory events. 5 Recombinant human interferon alfa (IFN-α) and the cytokine interleukin-2 (IL-2) were approved for the adjuvant immunotherapy of patients with resected high-risk melanoma in 1992 and 1998, respectively.…”
Section: Introductionmentioning
confidence: 99%